A review of telerehabilitation for cardiac patients. (January 2015) - Frederix, Ines; Vanhees, Luc; Dendale, Paul; Goetschalckx, Kaatje
We conducted a literature review of telerehabilitation interventions on cardiac patients. We searched for studies evaluating some form of telerehabilitation in cardiac patients. A total of 116 publications were screened initially, of which 37 publications were eligible for further review. We assessed study strength, based on the level of evidence and the quality of the intervention. The majority of the articles (70%) represented the highest level of evidence. Most interventions were of good (46%) or fair (51%) quality. Most studies evaluated the efficacy of the telerehabilitation interventions (84%), while 38% reported on feasibility and acceptance. Most studies did not include safety and/or cost-benefit analyses. Most telerehabilitation interventions (90%) employed only one or two core components of cardiac rehabilitation (CR). Of the CR core components, physical activity was most frequently evaluated. Telerehabilitation appears to be a feasible and effective additional and/or alternative form of rehabilitation, compared to conventional in-hospital CR. Evaluations of telerehabilitation programmes taking into account patient safety and health economics are now required.